Psikologi Investor Dalam Mengambil Keputusan Berinvestasi - Lutfi Alhazami (Universitas Mercu Buana Jakarta, 2019)
This Research aims to help investors psychologically in make investment decisions. The purpose is to look at the psychological factors of excessive investor making investment decisions. It is suspected that overconfidence bias has a positive effect on investment decision and optimism bias has a positive effect on investment decision. This is quantitative research, data collection technique from a questionnaire distributed to 150 young investors in West Jakarta. Classic Assumptions, multiple linear regression analysis, hypothesis testing is used in this research. The results show that over confidence bias has a positive effect on investment decision and optimism bias has a positive effect on investment decision.